A new design of luminescent solar concentrator and its trial run - Wang, C.; Abdul-Rahman, H.; Rao, S.P. (John Wiley & Sons, 2010)
Normal luminescent solar concentrators (LSC) have a great limitation in their light transportation because the light produced by the recently reported LSCs is not a point light source. In order to enable LSCs to use optical fibers as the effective remote light transport media, a new design of LSC, which uses three color luminescent fibers for solar absorption and uses clear optical fiber bundles to transport the absorbed sunlight into a remote place, is fabricated and tested. Radiation flux ratios with a mean value of 5.7%, the luminous flux up to 114.1 lumens, and the light efficiency of 0.56% have been achieved during the trial run. The luminous efficacy as 0.643 lm W(-1) is higher than that of combusting candles (0.3 lm W(-1)) but lower than that of the incandescent light bulbs (16-40 lm W(-1)). Further, since the sun light is free, different from electrical light sources, the luminous efficacy of the new LSC does not result in any electricity consumption when it is under operation. A color analysis and spectrum test proves that the light produced by the new LSC performs a great match to the direct sun light in color. Copyright (C) 2010 John Wiley & Sons, Ltd.